Hirsutella sinensis Treatment Shows Protective Effects on Renal Injury and Metabolic Modulation in db/db Mice. (4th April 2019) - Lu, Zhenyao; Li, Sijia; Sun, Runbin; Jia, Xue; Xu, Chen; Aa, Jiye; Wang, Guangji
Abstract : Hirsutella sinensis (HS) is the anamorph of the traditional Chinese medicine Cordyceps sinensis . Although the renal protective effect of HS has been reported, its effect on diabetic nephropathy (DN) remains unclear. In this study, db/db mice were used as the DN model, and the renal protective effect was evaluated after oral administration of HS for 6 and 12 weeks. Plasma, urine, and kidney samples were collected, and biochemical indicator measurements, pathological analysis, and metabolomics studies were performed. Biochemical assays showed that HS reduced the levels of fasting blood glucose (FBG), urinary albumin/creatinine ratio (ACR), and N-acetyl-beta-D-glucosaminidase (NAG) and increased the creatinine clearance (Ccr). HS alleviated glomerular and tubular glycogen accumulation and fibrosis and normalized the disordered ultrastructure of the glomerular filtration barrier. Metabolomics analysis of metabolites in the plasma, urine, and kidney indicated that HS modulated the perturbed glycolipid metabolism and amino acid turnover. HS reduced the elevated levels of metabolites involved in energy metabolism (TCA cycle, glycolysis, and pentose phosphate pathway) and nucleotide metabolism (pyrimidine metabolism and purine metabolism) in the kidneys of db/db mice. These results suggest that HS can protect against renal injury and that its efficacy involved metabolic modulation of the disturbed metabolome in db/db mice.